Effect of tree legumes in hedgerows on soil fertility changes and crop performance in the semiarid highlands of Rwanda - Balasubramanian, V.; Sekayange, L. (Informa UK Limited, 1991)
The soil fertility improvement potential of five tree legumes as alley hedges was studied on a Ultic Haplustox soil at a semi-arid highland site in Rwanda from 1983 to 1989. Tree species tested were C. calothyrsus Meissn., C. spectabilis DC, L. diversifolia (Lam.) de Wit., L. leucocephala (Lam.) de Wit. and S. sesban (L.) Merr.; they grew to a height of 1.01 to 2.15 m and 2.85 to 3.37 m, after 1 and 1.5 years respectively. S. sesban could not withstand intensive pruning (four times per year) and 83% of the trees died after the six prunings. In contrast, C. calothyrsus lost only 28%, both species of Leucaena 9 to 10%, and C. spectabilis none of the trees after 18 prunings in 4.5 years. Above-ground biomass production increased steadily with the age of the trees. Mean values for 1984–89 were: 5.6 to 7.3 Mg/ha dry weight of leaf biomass and 3.7 to 5.0 Mg/ha of wood. Mean annual nutrient addition to soil through leaf biomass was: 72 to 119 kg/ha of N, 2 to 3 of P, 47 to 94 of Ca, 8 to 19 of Mg, and 29 to 60 of K, and it was equivalent to an application of 10 Mg/ha/year of cattle manure. Tree mulch application reduced the rate of soil fertility decrease due to cropping; percent increases over control were 2 to 20 for soil C, −3 to 7 for K, 4 to 51 for Ca, 7 to 31 for Mg, and 3 to 47 for exchange capacity in mulched plots. Combined application of leaf biomass and manure increased the soil pH (water) by 0.4 to 0.5 units, K by 0 to 0.7 mmol, Ca by 10.8 to 17.6 mmol and Mg by 0.5 to 2.3 mmol and exchange capacity by 10.5 to 34.0 mmol above the level of soils cleared from the savanna vegetation. Mean nutrient export from the site in woody stems ranged from 17 to 28 kg/ha/year of N, 1 to 2 of P, 13 to 16 of Ca, 2 to 5 of Mg, and 17 to 34 of K. Grain yield increase of beans (Phaseolus vulgaris L.) and sorghum (Sorghum bicolor L.) to tree foliage application was the largest in C. spectabilis alleys, followed by the others. Crop yield increases due to tree mulch use were less in manured plots. Maize {Zea mays L.) response was poor. Tuber yield of sweet potato (Ipomoea batatas (L.) Lam.) decreased when planted in alleys, due to the lower tuber yield per unit crop area in alleys than in the control and a 14 to 32% yield fall off at the tree/crop interface.